Methylated Re(i) tetrazolato complexes: photophysical properties and Light Emitting Devices1. Issue 18 (14th May 2015) - Werrett, Melissa V.; Huff, Gregory S.; Muzzioli, Sara; Fiorini, Valentina; Zacchini, Stefano; Skelton, Brian W.; Maggiore, Antonio; Malicka, Joanna M.; Cocchi, Massimo; Gordon, Keith C.; Stagni, Stefano; Massi, Massimiliano
<x xml:space="preserve">Abstract</x> Methylated Re(i) tetrazolato complexes are suitable as phosphors for Light Emitting Devices.